Metrološko ovrednotenje merilnega sistema DEMOS - Anton Nino, Bratina Novak (Elektrotehniški vestnik, 2025)
This paper presents a metrological evaluation of the DEMOS measurement system, designed for monitoring indoor and outdoor environmental conditions, especially in classrooms. DEMOS integrates digital environmental sensors and an ESP32 microcontroller, measuring temperature, humidity, noise, CO2, VOCs, PM, and other pollutants. Temperature and humidity were evaluated using SEN55 and SCD40 sensors in a climatic chamber, and results show that SEN55 performs better in both stability and accuracy. The expanded uncertainty for temperature is 0.50?°C for SEN55 and 0.62?°C for SCD40, while for humidity it is 4.0?% r.h. and 7.1?% r.h., respectively. Noise measurements revealed that although DEMOS cannot replace class 1 sound level meters, it provides reliable trend detection within the speech frequency range. The system is compact, scalable, and suitable for spatial environmental assessment and long-term monitoring, particularly where relative changes and spatial variability are more relevant than absolute precision.
Keywords: environmental parameters; hrup; humidity; measurement system; merilni sistem; noise; okoljski parametri; temperatura; temperature; vlaga